2018
DOI: 10.1093/mnras/sty2114
|View full text |Cite
|
Sign up to set email alerts
|

Bending waves in the Milky Way’s disc from halo substructure

Abstract: We use N-body simulations to investigate the excitation of bending waves in a Milky Way-like disc-bulge-halo system. The dark matter halo consists of a smooth component and a population of subhaloes while the disc is composed of thin and thick components. Also considered is a control simulation where all of the halo mass is smoothly distributed. We find that bending waves are more vigorously excited in the thin disc than the thick one and that they are strongest in the outer regions of the disc, especially at … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 87 publications
(152 reference statements)
5
38
0
Order By: Relevance
“…Nevertheless, the total stellar disc mass is consistent with other estimates (e.g., Bovy & Rix 2013). Overall, our choices of component profiles and the values of their corresponding parameters define a valid model for the Galaxy, comparable to the model successfully adopted by others in numerical studies (e.g., Chequers et al 2018). Our interaction models consist essentially of a twocomponent (DM, stellar spheroid) system orbiting an initially isolated Galaxy along an (unrealistic) hyperbolic orbit.…”
Section: N-body Simulationssupporting
confidence: 87%
“…Nevertheless, the total stellar disc mass is consistent with other estimates (e.g., Bovy & Rix 2013). Overall, our choices of component profiles and the values of their corresponding parameters define a valid model for the Galaxy, comparable to the model successfully adopted by others in numerical studies (e.g., Chequers et al 2018). Our interaction models consist essentially of a twocomponent (DM, stellar spheroid) system orbiting an initially isolated Galaxy along an (unrealistic) hyperbolic orbit.…”
Section: N-body Simulationssupporting
confidence: 87%
“…Springel et al 2008). Their collective effect of the subhalo mass function has been proposed to excite bending waves in the disc in numerical experiments by Chequers et al (2018), however we note that these used initial conditions which did not model this effect correctly. Indeed such experiments have used velocity distribution functions similar to that of the underlying parent halo, which is not representative of cosmologically formed Galactic dark matter halos (Sawala et al 2017) Figure 17.…”
Section: Other Perturbers?mentioning
confidence: 93%
“…Studies of flaring HI gas in the outer galaxy also support a prolate DM distribution (Banerjee & Jog 2011); these authors note that a prolate halo can support long-lived warps (Ideta et al 2000), which would help to explain why they are commonly seen (Banerjee & Jog 2011). It has also been suggested that some of these features could arise from a dynamically active disk (Chequers et al 2018) in isolation. Others note that ridges in phase-space may also connect to the Galactic bar (Mühlbauer & Dehnen 2003;Fragkoudi et al 2019).…”
Section: Introductionmentioning
confidence: 93%